Retrospective case review of missed opportunities for primary prevention of stroke and TIA in primary care: protocol paper. Issue 11 (11th November 2014) - Moran, Grace M; Calvert, Melanie; Feltham, Max G; Marshall, Tom
Abstract : Introduction: Stroke is a major health problem and transient ischaemic attack (TIA) is an important risk factor for stroke. Primary prevention of stroke and TIA will have the greatest impact on reducing the burden of these conditions. Evidence-based guidelines for stroke/TIA prevention identify individuals eligible for preventative interventions in primary care. This study will investigate: (1) the proportion of strokes/TIAs with prior missed opportunities for prevention in primary care; (2) the influence of patient characteristics on missed prevention opportunities and (3) how the proportion of missed prevention opportunities has changed over time. Methods and analysis: A retrospective case review will identify first-ever stroke and patients with TIA between 2000 and 2013 using anonymised electronic medical records extracted from the health improvement network (THIN) database. Four categories of missed opportunities for stroke/TIA prevention will be sought: untreated high blood pressure in patients eligible for treatment (either blood pressure ≥160/100 or ≥140/90 mm Hg in patients at high cardiovascular disease (CVD) risk); patients with atrial fibrillation with high stroke risk and no anticoagulant therapy; no lipid modifying drug therapy prescribed in patients at high CVD risk or with familial hypercholesterolaemia. The proportion of patients with each missed opportunity and multiple missed opportunities will be calculated. Mixed effect logistic regression will model the relationship between demographic and patient characteristics and missed opportunities for care; practice will be included as a random effect. Ethics and dissemination: THIN data collection was approved by the NHS South East Multi-centre Research Ethics Committee (MREC) in 2003. This study was approved by the independent scientific review committee in May 2013. Dissemination of findings has the potential to change practice, improve the quality of care provided to patients and ultimately reduce the incidence of strokes and TIAs. Findings will be published in a peer-reviewed journal and disseminated at national and international conferences.